Implementation of Techno-Edutourism for Smart Farming and Digital Branding in Islamic Boarding Schools Toward a Sustainable Economy - Rahman, Khaidir; Hambali, Amiruddin; Ilham, Ilham; Novitasari, Ervi; Hasrul, M. Reza (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented at SMKS Pesantren Alam Indonesia (PAI) Barru, South Sulawesi, the only Islamic boarding vocational school in agriculture committed to producing graduates who are both spiritually and technically competent. The area’s potential, such as approximately 5 hectares of fertile land, agricultural practice facilities, and strong social support from the local community, makes it ideal for developing a pesantren-based techno-edutourism center. However, resource management remains conventional and has not yet integrated modern technologies. The main problems include the absence of an Internet of Things (IoT)-based monitoring system, the lack of a modern irrigation system, and limited digital promotion for edutourism management. To address these challenges, the program applied the Service Learning (SL) approach, which integrates academic learning with direct community engagement. The implementation involved lectures, demonstrations, and participatory discussions, structured into three stages: preparation, training and hands-on practice, and evaluation. The activities focused on introducing agricultural drone technology, IoT-based monitoring systems, and the development of automated irrigation systems, complemented by digital branding simulations for edutourism. The results indicate an increase in teachers’ and students’ knowledge of smart farming, improved efficiency in agricultural practices, and the establishment of a digital promotion system to support edutourism development. This program contributes to five Sustainable Development Goals (SDGs), namely SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), SDG 12 (Responsible Consumption and Production), and SDG 17 (Partnerships for the Goals), while also serving as a sustainable pesantren empowerment model that can be replicated in other regions.